Determinan Kepuasan Pengguna Sistem Informasi Akademik (Determinants of User Satisfaction with Academic Information Systems) - Lating, Ali; Lating, Fadil Abdullah; Sugiono, Djoko; Liana, Yuyuk (STIE Malangkucecwara, 2021)
This study aims to analyze the factors that affect the satisfaction of users of academic information systems. The factors tested in this study were: system quality, information quality, and perceived usefulness. The research population is STIE Malangkuçeçwara students batch 2014, with a sample of 193 respondents as users of academic information systems. Data was collected using a questionnaire distributed through mass media (WhatsApp and Line). Data were analyzed using partial least squares. The results showed that the quality of information, system quality and perceived usefulness affect user satisfaction.